Endurance at the Top: Gender and Political Ambition of Spanish and Swedish MPs. Issue 3 (21st July 2016) - Galais, Carol; Öhberg, Patrik; Coller, Xavier
Abstract : The gender gap in political ambition is an important explanation for the absence of women in legislative assemblies. However, previous research on this matter is limited by two facts: it is conducted mostly in the United States and does not pay much attention to cultural and institutional factors. In this article, we test the extent to which established mechanisms behind female politicians' career ambitions—such as differentiated political socialization and family support for men and women—are related to gender inequality among parliamentarians. We also draw attention to other lesser-known aspects, such as political culture and gender policies. To do so, we compare Spain and Sweden, two countries with a relatively high number of female members of parliament (MPs) but different cultures and gender policies. We make use of two representative surveys on Swedish and Spanish MPs. The results show that female MPs in Spain have to sacrifice their family life more than Spanish males and Swedish MPs regardless of sex. In addition, Spanish female MPs' long-term political ambitions are more dependent on family support. Female MPs' ambition in Sweden, in turn, is highly influenced by a politicized upbringing.